Advancements in new desulfurization technology for industry scale applications - Sophia June C. Ng; Angelo Earvin Sy Choi (Results in Engineering)
The environmental hazards and health risks that sulfur causes have encouraged governments worldwide to lower their permissible fuel concentrations to prevent further damage. This is accomplished through desulfurization, a method of extracting sulfur from fuel to be used in other products such as sulfuric acid or elemental sulfur. The conventional method for desulfurization is hydrodesulfurization (HDS), which uses hydrogen to extract sulfur as hydrogen sulfide. It can effectively remove simple sulfur compounds but struggles with organic sulfur compounds due to steric strain. This can be overcome through multibed reactors, increasing temperature and pressure, and modified catalysts. However, these leave HDS more susceptible to competing reactions, dangerous process conditions, and reactor fouling. Research has shifted to searching for alternative or supplementary processes to create a safer and more efficient process. Oxidative desulfurization (ODS) is one of these novel methods with 3500 Scopus-indexed articles and 26,000 patents in Google Patents. Catalyst modifications such as photocatalytic oxidative desulfurization (PODS), ionic liquid-oxidative desulfurization (IL-ODS), and zeolite/metal organic framework (MOF) supports can reduce reaction time to minutes and allow for several cycles of reuse with maintained efficiency. These parameters can be further optimized through novel reactor design but few studies have discussed this impact. The review also discusses current industrialization efforts for ODS. Some of the shortcomings found were the cost-effectiveness, catalyst recyclability, and process optimization. These make it difficult to create and maintain industrial-scale ODS at the current research level.